ANALISIS PENGENDALIAN KUALITAS DALAM MENINGKATKAN PRODUKTIVITAS PADA UMKM RAJA NAGA LAUNDRY DI KOTA MEDAN - Veri Sangap Tua Pasaribu; Hannes Inmanuel Sinaga; Luna Maya Sitepu; Ega Grace Nichol Sitindaon; Tasya Novi Ardana; Putri Kemala Dewi Lubis (STKIP Subang, 2026)
ABSTRACT This study aims to analyze the implementation of quality control in improving productivity at Raja Naga Laundry. The research used a descriptive qualitative approach. Data collection techniques were conducted through observation, interviews, and documentation. The results of the study indicate that the laundry business has implemented quality control through employee training, work supervision, customer clothing inspection, and routine machine maintenance. These efforts were carried out to maintain service quality and support operational productivity. However, several obstacles were still found, such as machine damage, power outages, mistakes in recording customer clothes, and customer complaints regarding fragrance and drying results. The implementation of quality control was able to help reduce work errors and improve employee productivity in operational activities. Therefore, improving supervision systems and service quality is necessary to support better productivity and customer satisfaction in laundry businesses.